Answer:
f(2) = -2
Step-by-step explanation:
plug in 2 to wherever x is in this statement:
f(2) = -2(2^2) - 2(2) + 10
f(2) = -2(4) - 4 + 10
f(2) = -8 - 4 + 10
f(2) = -2
Answer:
34.35
Step-by-step explanation:
Answer:
-1/5
Step-by-step explanation:
Answer:
=(x-2)/3(x+4)
Step-by-step explanation:
F(x)=x²-3x+2/3x²+9x-12
Using mid term break formula
=x²-2x-x+2/3(x²+3x-4)
=x(x-2)-1(x-2)/3(x²+4x-x-4)
=(x-2)(x-1)/3{x(x+4)-1(x+4)}
=(x-2)(x-1)/3(x-1)(x+4)
Cancelling (x-1)
We get
=(x-2)/3(x+4)
Hope it helps :)